Etnosains pada Proses Pengolahan Lemang Kancung Beruk (Kantong Semar) Kerinci - Fatimah, Suci Nuriya; Ikhwal, Muhammad; Minarsih, Minarsih; Surati, Surati; Musyaddad, Muhammad (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2023)
This study aims to examine the process of processing kerinci lemang kancung which can be integrated into science learning based on local wisdom. So that later the results of this study can be used as reference material in learning science based on local wisdom. This study uses a qualitative method of ethnographic research. This research was conducted in Lempur Village, Kerinci Regency. The instruments used in this study were observation sheets, interview guides. Observation sheet indicators include the type of pitcher plant used, materials and tools, and the process of cooking lemang and the philosophy of lemang kancung beruk kerinci. During the steaming process, the temperature will be measured using a laser thermometer. The interview guide contains questions that will be asked of scientific experts, customary leaders and kerinci lemang kancung makers. The data analysis technique was carried out in a qualitative descriptive manner with the Miles and Huberman model consisting of several stages, namely data reduction, data presentation and conclusion/verification.